S123 Mononuclear inflammation and disruption of normal alveolar structure following deletion of Gαq/11, but not Gα12/13, in type II alveolar epithelial cells. (16th November 2010) - John, A E; Porte, J; Jolly, L; Tatler, A L; Jenkins, R G
Abstract : Activation of latent TGFβ by the epithelially restricted αvβ6 integrin is induced by activators of the RhoA signalling pathway and is critical in the pathogenesis of lung injury and fibrosis. The G-proteins, Gα12 and Gα13 are known to activate RhoA and we have previously shown that the αvβ6 integrin can mediate TGFβ activation via Gαq and RhoA. To establish the role of these G-proteins in both normal lung development and following lung injury, we generated mice with a targeted deletion of Gαq/11 or Gα12/13 in SpC-positive Type II alveolar epithelial cells. SpC-Cre mice were crossed with either Gαq(flox-flox)/11(-/-) or Gα12(-/-)/13(flox-flox) mice and the lungs analysed histologically at 6 and 8 weeks after birth. At 6 weeks, lungs from mice with a homozygous deficiency in SpC-Gαq/11 contained focal inflammatory infiltrates consisting primarily of mononuclear leukocytes. Inflammation was associated with the localised disruption of normal alveolar architecture and the appearance of abnormal Type I and Type II alveolar epithelial cells, identified by SpC and T1α immunohistochemistry, within in the alveolar airspaces. Furthermore, immunohistochemical analysis of phosho-Smad2 levels in these lungs detected increased staining in the inflammatory foci within the homozygous SpC-Gαq/11 knockout lungs. At 8 weeks, the inflammatory foci were more numerous and lung architecture was severely disrupted with multiple abnormally large alveolar airspaces detected. In contrast, mice with at least one floxed Gαq or null Gα11 allele showed no abnormalities at either 6 or 8 weeks. We also detected no abnormal lung phenotype in 6- and 8-week old mice with a homozygous or heterozygous deficiency in SpC-Gα12/13. These data suggest that Gα11/q signalling is required to prevent pulmonary inflammation and our findings would be consistent with impaired epithelial TGFβ activation in the lungs of these mice. Further studies are required to determine the origin of the cells activating TGFβ in these lungs.